Development Of Laboratory Work Instruction For Junior High School: Borax Content Identification Using Natural Indicators - Rahman, Nanang; Abhi Purwoko, Agus; Muntari, (International Journal of Scientific Research and Management (IJSRM), 2019)
The main goal of this study is to develop a laboratory work instruction for junior high school, in particular in identification of non food additives, such as borax, in daily foodstuff. The method of development is referred to a four-step procedure by Borg and Galls. There are 94 samples of extract of leafs and flowers of various tropical plants that have been examined for identification of borax. Of these samples it is found that there are 4 flower extracts that indicate sensitivity to the borax content, namely Ruellia Simplex, Curcuma Longa, Plumeria Ruba, and Portulaca Grandiflora. In later stage of development the laboratory instruction were validated by academic experts and school teachers. The results of validation indicate that the guideline is suitable to be implement in laboratory works at junior high school.